The Relationship Between Proactive Behavior and Work-Family Conflict: A Moderated Mediation Model - Cui, Zilong; Li, Yuyin (Frontiers in Psychology, 2021)
This study aims to explore the linking mechanisms and conditional processes underlying the relationship between proactive behavior and work-family conflict. Considering conservation of resources theory, we argue that workplace anxiety mediates the relationship between proactive behavior and work-family conflict. Furthermore, we suggest that immediate supervisor perspective taking and employee emotional intelligence moderate this proposed indirect effect. Two-wave, multisource lagged data were collected from 450 employees of 7 domestic Chinese firms to examine the hypothesized moderated mediation model. Our findings support the hypothesis that proactive behavior is positively related to work-family conflict and that workplace anxiety partially mediates this relationship. Immediate supervisor perspective taking moderates the positive association of proactive behavior with workplace anxiety and the indirect relationship between proactive behavior and work-family conflict through workplace anxiety. Emotional intelligence moderates the positive association of proactive behavior with workplace anxiety and the indirect relationship between proactive behavior and work-family conflict through workplace anxiety. The results deepen our theoretical understanding of the consequences of proactivity by demonstrating the positive associations between proactive behavior and work-family conflict. The current study also contributes to the literature by identifying workplace anxiety as a mediating mechanism explaining the relationship between proactivity and work-family conflict. Furthermore, supervisor perspective taking and employee emotional intelligence moderate the above mediating effect.